Self-imposed pressure or joyful learning: emotions of Chinese as a foreign language learners in feedback on academic writing - Liu, Ruoxi; Xin, Ping (Frontiers in Psychology, 2025)
Although writing feedback is widely believed to elicit a range of emotions, studies on the emotional experiences of L2 students with this teaching and learning tool, as well as their regulation strategies, remain largely underexplored. Drawing on the analytical framework of academic emotions from the perspective of positive psychology, this study examines two Chinese as foreign language (CFL) students’ emotional reactions to their teacher’s oral and written feedback and their emotion regulation strategies. The main data includes interviews, retrospective oral reports, students’ reflection journals, academic writings, and teacher feedback. The study found that feedback aroused students’ academic achievement emotions, cognitive emotions, and social emotions across various dimensions of valence and activation. Over the course of three feedback processes within one semester, the two learners’ emotions gradually became neutral or positive. They effectively employed emotion-oriented, appraisal-oriented, and situation-oriented strategies to manage negative emotions and adapt to feedback. The findings suggest that paying attention to the intrinsic values of feedback may help learners experience more positive academic emotions, while paying too much attention to its extrinsic values may lead to negative emotions.